A Finnish founder mutation in RAD51D: analysis in breast, ovarian, prostate, and colorectal cancer. Issue 7 (31st May 2012) - Pelttari, Liisa M; Kiiski, Johanna; Nurminen, Riikka; Kallioniemi, Anne; Schleutker, Johanna; Gylfe, Alexandra; Aaltonen, Lauri A; Leminen, Arto; Heikkilä, Päivi; Blomqvist, Carl; Bützow, Ralf; Aittomäki, Kristiina; et al.
Abstract : Background: RAD51D and RAD54L are involved in homologous recombination, and rare mutations in RAD51D were recently found in breast-ovarian cancer families. This study investigated RAD51D and RAD54L for mutations in breast and ovarian cancer patients in the Finnish population. Methods: The study sequenced the RAD51D and RAD54L genes in 95 breast and/or ovarian cancer families and genotyped the identified mutation in an additional 2200 breast and 553 ovarian cancer patients and 2102 population controls. To investigate the role of the mutation in other common cancers, 1094 prostate and 980 colorectal cancer patients were genotyped. Results: In the screening of RAD51D, one deleterious founder mutation c.576+1G>A was identified in two breast-ovarian cancer families. No mutations were found in RAD54L . Altogether, the c.576+1G>A mutation was detected in 5/707 patients with a personal or family history of ovarian cancer (OR 9.16, 95% CI 1.07 to 78.56; p=0.024), with the highest frequency among breast-ovarian cancer families (3/105 vs 1/1287 controls, OR 37.82, 95% CI 3.90 to 366.91; p=0.0016), but no elevated frequency among breast cancer patients/families (2/2105, p=1). The mutation was not found among prostate or colorectal cancer patients. Conclusions: The results of this study on familial and unselected breast, ovarian, colorectal, and prostate cancer patients suggest that RAD51D is primarily a moderate penetrance susceptibility gene for ovarian cancer, with clinical significance for the carriers.